Issues and challenges in medical tourism: an interdisciplinary perspective - Abd. Manaf, Noor Hazilah; Hussin, Husnayati; Jahn Kassim, Puteri Nemie; Alavi, Rokiah; Dahari, Zainurin (2013)
Medical tourism is a new and exciting industry due to its rapid growth and huge economic potential, estimated to be worth USD 4 billion for the Asian chapter (Deloitte, 2008). Malaysia is joining the bandwagon with Thailand, Singapore and India being the main medical tourist destination countries in Asia. Factors such as excessive medical costs in rich countries, long waiting lists, relative affordability of international air travel, favourable economic exchange rates, and the ageing of the affluent baby-boomer generation has contributed to the growth of the industry. Convergence in global healthcare standard also meant that hospitals in other parts of the world can be as good, if not better, than those in the developed west. While the industry holds much promise, issues and challenges faced need to be addressed. The paper explores challenges from human resource, trade, information technology and legal perspectives. The large presence of medical tourists also do place pressure and demand on existing healthcare system. Thus, there is a need to balance the welfare and well-being of Malaysians at large against the extra income generated by medical tourism.